2021
DOI: 10.7759/cureus.16383
|View full text |Cite
|
Sign up to set email alerts
|

A COVID-Positive 52-Year-Old Man Presented With Venous Thromboembolism and Disseminated Intravascular Coagulation Following Johnson & Johnson Vaccination: A Case-Study

Abstract: The coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Infection by the SARS-CoV-2 increases the risk for systematic multi-organ complications and venous, arterial thromboembolism. The need for an effective vaccine to combat the pandemic prompted the Centers for Disease Control and Prevention (CDC) and Food and Drug Administration (FDA) to approve a nationwide distribution of the Ad26.COV2.S vaccine manufactured by Johnson & Johnson (J&J). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The aforementioned authors also reported that 19 of 20 hospitalized patients aged 22–73 years (11 females and 8 males) showed petechiae, bruising, or mucosal bleeding in 1–23 days post Pfizer (9 patients) and Moderna (11 patients) vaccination, along with platelet counts mostly ≥10 × 10 9 /L (range 1–36 × 10 9 /L; median 2 × 10 9 /L). The vaccine-induced ITP could possibly have similar pathogenicity to COVID-19 vaccine-induced DIC, which highlights the importance of further investigation in agreement with others [ 17 ]. Recently, a new phenomenon characterized by ITP was reported in multiple patients after vaccination with the ChAdOx1 nCoV-19.…”
Section: Introductionsupporting
confidence: 84%
“…The aforementioned authors also reported that 19 of 20 hospitalized patients aged 22–73 years (11 females and 8 males) showed petechiae, bruising, or mucosal bleeding in 1–23 days post Pfizer (9 patients) and Moderna (11 patients) vaccination, along with platelet counts mostly ≥10 × 10 9 /L (range 1–36 × 10 9 /L; median 2 × 10 9 /L). The vaccine-induced ITP could possibly have similar pathogenicity to COVID-19 vaccine-induced DIC, which highlights the importance of further investigation in agreement with others [ 17 ]. Recently, a new phenomenon characterized by ITP was reported in multiple patients after vaccination with the ChAdOx1 nCoV-19.…”
Section: Introductionsupporting
confidence: 84%
“…In a multinational study of 21,720 persons receiving the Comirnaty (Pfizer/BioNTech) vaccine, half of them followed for 2 months and reported no deep venous thrombosis (DVT) or pulmonary embolism (PE) 2279 . Shazley et al, reported on a patient who developed DVT and PE which culminated in disseminated intravascular coagulation (DIC) in a COVID - 19 positive patient following the administration of the J&J vaccine 2280 . Smadja et al, assessed clinical features of venous and arterial thrombotic events after injection of three COVID - 19 vaccines (Comirnaty, Moderna, and Vaxzevria).…”
Section: - Does the Risk For Vte Increase After Covid - 19 Vaccination?mentioning
confidence: 99%
“…However, to date, the amount of data on such adverse effects is too small to provide clear evidence of causation. At the same time, Johnson & Johnson’s recombinant adenosis vector vaccine was also suspended by FDA due to rare blood-related problems in some people, namely thrombocytopenia syndrome thrombosis, resulting in cerebral venous sinus thrombosis (CVST) [ 42 , 43 , 44 , 45 ]. Overall, these life-threatening serious adverse events are rare, so ongoing global vaccination programmes should still be supported.…”
Section: Discussionmentioning
confidence: 99%